Anda di halaman 1dari 17

# Section 3.

## Indeterminate Forms and LHospitals Rule

THEOREM (LHospitals Rule): Suppose f and g are differentiable and g (x) 6= 0 near a
(except possibly at a). Suppose that
lim f (x) = 0 and

xa

lim g(x) = 0

xa

or that
lim f (x) = and

xa

lim g(x) =

xa

or
.) Then
0

f (x)
f (x)
= lim
xa g (x)
xa g(x)
lim

## Indeterminate Forms of Type

EXAMPLES:
5x 2
.
1. Find lim
x 7x + 3

and
0

Solution 1: We have
5x 2 h i
= lim
=
x
x 7x + 3

lim

5x2
x
7x+3
x

5x
x
x 7x
x

= lim

2
x
3
x

5
x 7 +

= lim

2
x
3
x

5
50
=
7+0
7

Solution 2: We have
5x 2 h i
(5x 2)
(5x) 2
5x 2
lim
= lim
=
=
lim
=
lim
x 7x + 3
x (7x + 3)
x (7x) + 3
x 7x + 3

5
5
510
= lim =
x 7
x 7 1 + 0
7

= lim
In short,

5
(5x 2)
5
5x 2
= lim
= lim =

x (7x + 3)
x 7
x 7x + 3
7
lim

x5 + x4 + x3 + x2 + x + 1
.
x 2x5 + x4 + x3 + x2 + x + 1

2. Find lim

## 2010 Kiryl Tsishchanka

x5 + x4 + x3 + x2 + x + 1
.
x 2x5 + x4 + x3 + x2 + x + 1

2. Find lim

Solution 1: We have
hi
x5 + x4 + x3 + x2 + x + 1
= lim
=
lim
x
x 2x5 + x4 + x3 + x2 + x + 1

4
3
2
x5
+ xx5 + xx5 + xx5 + xx5 + x15
x5
lim 5
4
3
2
x 2x + x + x + x + x + 1
x5
x5
x5
x5
x5
x5

1+0+0+0+0+0
1
=
2+0+0+0+0+0
2

1+
x 2 +

= lim

## x5 +x4 +x3 +x2 +x+1

x5
2x5 +x4 +x3 +x2 +x+1
x5
1
x
1
x

+
+

1
x2
1
x2

+
+

1
x3
1
x3

+
+

1
x4
1
x4

+
+

1
x5
1
x5

Solution 2: We have
hi
(x5 + x4 + x3 + x2 + x + 1)
x5 + x4 + x3 + x2 + x + 1
=
lim
=
x (2x5 + x4 + x3 + x2 + x + 1)
x 2x5 + x4 + x3 + x2 + x + 1

hi
(5x4 + 4x3 + 3x2 + 2x + 1)
5x4 + 4x3 + 3x2 + 2x + 1
=
lim
= lim
=
x (10x4 + 4x3 + 3x2 + 2x + 1)
x 10x4 + 4x3 + 3x2 + 2x + 1

20x3 + 12x2 + 6x + 2 h i
(20x3 + 12x2 + 6x + 2)
= lim
=
lim
=
x 40x3 + 12x2 + 6x + 2
x (40x3 + 12x2 + 6x + 2)

hi
(60x2 + 24x + 6)
60x2 + 24x + 6
= lim
= lim
=
x (120x2 + 24x + 6)
x 120x2 + 24x + 6

120x + 24 h i
120
1
(120x + 24)
120
= lim
= lim
=
=
lim
=
=
x 240x + 24
x (240x + 24)
x 240

240
2
lim

x+2
.
x2 ln(x + 3)

3. Find lim

Solution: We have

 

x+2
0
(x + 2)
lim
= lim
=
=
lim
x2 ln(x + 3)
x2 (ln(x + 3))

0
x2
= lim

x2

(x + 2)
1
(x + 3)
x+3

= lim

x2

x + 2
1
(x + 3 )
x+3

1 (x + 3)
1
x+3
1+0
= lim (x + 3)
= lim
= lim
= lim
1
1
1
x2
x2
x2
x2

1
(1 + 0)
(x + 3)
x+3
x+3
x+3
= 2 + 3 = 1

In short,
x+2
(x + 2)
1
= lim
= lim
= lim (x + 3) = 1

x2 ln(x + 3)
x2 (ln(x + 3))
x2 (x + 3)1
x2
lim

3x
.
x x2 + x 1

4. Find lim

## 2010 Kiryl Tsishchanka

3x
4. Find lim 2
.
x x + x 1

Solution: We have
hi
hi
3x
(3x )
(3x ln 3)
3x ln 3
lim 2
= lim 2
=
lim
=
=
lim
=
x x + x 1
x (x + x 1)
x (2x + 1)
x 2x + 1

ln 3 3x ln 3
ln 3 (3x )
= lim
= (D.N.E.)
x
x
2
2

= lim
ln x
5. Find lim .
x
x

Solution: We have
(ln x)
x1
ln x h i
x1 x
1
= lim 1/2 = lim 1 1/2 = lim 1 1/2
lim =
= lim 1 1/2 = 0
x (x
x x
x
x x
x

)
x x 2 x
2
2
6. Find lim

x0

5x tan 5x
.
x3

Solution 1: We have
 
5x tan 5x
0
(5x tan 5x)
5 sec2 5x (5x)
5 sec2 5x 5
lim
=
lim
=
=
lim
=
lim
x0
x0
x0
x0
x3
0
(x3 )
3x2
3x2

5
1 sec2 5x
5(1 sec2 5x)
=
lim
x0
3x2
3 x0
x2
1 sec2 5x
0
Since lim
is an indeterminate form of type , we can use LHospitals Rule again.
2
x0
x
0
But it is easier to do trigonometry instead. Note that 1 sec2 5x = tan2 5x. Therefore
= lim

sin 5x
sin 5x
5
5
5
5
1 sec2 5x
tan2 5x
tan2 5x
5
cos2 5x
1
lim
=
lim
=

lim
=

lim
=

lim
3 x0
x2
3 x0
x2
3 x0 x2
3 x0 x2
3 x0 x2
2
2

2
 


5
5
5
5
0
sin 5x
sin 5x
sin 5x
sin2 5x
= lim
= lim
5 lim
= lim 5
=
=
x0 5x
3 x0 x2
0
3 x0
x
3 x0
5x
3

2 

5
5
5
125
sin 5x
sin u
=
5 lim
= lim
= 1 = (5 1)2 = 25 =
5x0 5x
u0 u
3
3
3
3
In short,

5
5
5
5x tan 5x
(5x tan 5x)
1 sec2 5x
tan2 5x
sin2 5x
=
lim
=
lim
=

lim
=

lim
x0
x0
x3
(x3 )
3 x0
x2
3 x0 x2
3 x0 x2
2

5
sin 5x
125
5
= lim 5
= (5 1)2 =
3 x0
5x
3
3
lim

sin 5x
sin 5x
 
 
5x
5x
0
0
5x sin 5x
5x tan 5x
???
cos
5x
1
= lim
=
= lim
= lim
=
lim
3
3
3
3
x0
x0
x0
x0
x
0
x
x
x
0
 

0
(5 5 cos 5x)
125
5 5 cos 5x
25 sin 5x
= lim
= lim
= lim
=
= lim
=
3

2
2

x0
x0
x0
x0
(x )
3x
0
(3x )
6x
6
3

## 2010 Kiryl Tsishchanka

x + sin x
.
x x + cos x

7. Find lim

Solution 1: We have
x + sin x h i
= lim
=
lim
x
x x + cos x

x+sin x
x
x+cos x
x

x
lim x
x x
x

+ sinx x
1 + sinx x
= lim
x 1 + cos x
+ cosx x
x

sin x
cos x
= 0 and lim
= 0 by the Squeeze Theorem. Therefore
x
x
x
1 + sinx x
1+0
x + sin x
=
lim
= lim
=1
cos
x
x x + cos x
x 1 +
1+0
x

## Solution 2(???): We have

(x + sin x)
x + (sin x)
1 + cos x
x + sin x h i
=
lim
=
=
lim
=
lim
lim
x (x + cos x)
x x + (cos x)
x 1 sin x
x x + cos x

1 + cos x
does not exist. In fact, we first note that 1 + cos x
x 1 sin x
1 + cos x
and 1 sin x may attain any value between 0 and 2. From this one can deduce that
1 sin x
1 + cos x
attains any nonnegative value infinitely often as x . This means that lim
does
x 1 sin x
not exist, so LHospitals Rule cant be applied here.
One can show, however, that lim

8. Find lim
x

sin x
.
1 cos x

Solution(???): We have
lim

sin x
(sin x)
cos x
= lim
= lim
=

x sin x
1 cos x x (1 cos x)

This is WRONG. In fact, although the numerator sin x 0 as x , notice that the
denominator (1 cos x) does not approach 0, so LHospitals Rule cant be applied here. The
required limit is easy to find, because the function is continuous at and the denominator is
nonzero here:
sin x
sin
0
lim
=
=
=0
x 1 cos x
1 cos
1 (1)
sin x
.
x0 x

9. Find lim

Solution(???): We have
 
sin x
0
cos 0
1
(sin x)
cos x
lim
= lim
=
=
lim
=
=
=1
x0 x
x0
x0
0
x
1
1
1

The answer is correct, but the solution is WRONG. Indeed, the above proof is based on the
sin x
= 1 (see
formula (sin x) = cos x. But this result was deduced from the fact that lim
x0 x
Appendix A). So, the solution is wrong because it is based on Circular Reasoning which is a
logical fallacy. However, one can apply LHospitals Rule to modifications of this limit (see
Appendix B).
4

## Indeterminate Forms of Type and 0

EXAMPLES:
10. Find lim (x ln x).
x

Solution 1: We have




ln x
ln x
lim (x ln x) = [ ] = lim x 1 x
= lim x 1
x
x
x
x
x
Note that

ln x h i
(ln x)
x1
1
= lim
=
=
lim
= lim = 0

x x
x
x 1
x x

x


ln x
= lim x (1 0) = (D.N.E.)
lim (x ln x) = lim x 1
x
x
x
x
lim

therefore

Solution 2: We have
x

ex
= ln lim
x x


x1

(ex )
=
= ln lim
x x

1
1

ln x x 1

hi

ex
= ln lim
x 1


ex
x

= (D.N.E.)

x1

1
1

ln x x 1

## 2010 Kiryl Tsishchanka

Solution: We have




1
1 (x 1)
1
ln x 1
lim
= [ ] = lim

x1
x1 ln x (x 1)
ln x x 1
ln x (x 1)
 
x 1 ln x
0
(x 1 ln x)
= lim
= lim
=
x1 ln x(x 1)
x1 (ln x(x 1))
0
1
1
x 1 (ln x)
x
= lim
= lim
x1 (ln x) (x 1) + ln x (x 1)
x1 x 1
+ ln x
x


1
1
1
x
1x x
x
x
 = lim
= lim 
x1 x 1
x1
x1
x + ln x x
+ ln x x
x
x
 
(x 1)
0
x 1
x1
= lim
=
=
lim
= lim
x1 (x 1 + x ln x)
x1 x 1 + x ln x + x(ln x)
x1 x 1 + x ln x
0
10

= lim

x1

1 0 + 1 ln x + x

1
x

1
1
1
=
=
x1 2 + ln x
2+0
2

= lim

In short,

lim

x1

1
1

ln x x 1

1
1
x 1 ln x
(x 1 ln x)
x
= lim
= lim
= lim
x1 ln x (x 1)
x1 (ln x (x 1))
x1 x 1
+ ln x
x
1
(x 1)
1
x1
= lim
= lim
=

x1 (x 1 + x ln x)
x1 2 + ln x
x1 x 1 + x ln x
2

= lim

x0

## 12. Find lim+ (sin x ln x).

x0

Solution 1: We have
lim (sin x ln x) = [0 ] =

x0+

## (sin x)1 sin x ln x

sin x ln x
= lim+
lim+
x0
x0
1
(sin x)1 1

= lim+
x0

hi
ln x
= lim+
=
x0 (sin x)1

(ln x)
x1
x1
=
lim
=
lim
((sin x)1 ) x0+ (sin x)2 (sin x) x0+ (sin x)2 cos x

x1 x sin2 x
sin2 x
= lim+
= lim+
2
x0 (sin x)2 cos x x sin x
x0 x cos x

## We can now proceed in two different ways. Either



 
sin x sin x
0
sin2 x
= lim+
=

lim+
x0
x0 x cos x
0
x
cos x
= lim+
x0

sin x
sin 0
0
sin x
lim+
= 1
= 1 = 0
x0 cos x
x
cos 0
1

or
 
(sin2 x)
2 sin x cos x
0
sin2 x
= lim+
=
= lim+
lim+

x0 (x cos x)
x0 x cos x + x(cos x)
x0 x cos x
0
= lim+
x0

In short,

2 sin 0 cos 0
201
2 sin x cos x
=
=
=0
cos x x sin x
cos 0 0 sin 0
100

(ln x)
ln x
x1
=
lim
=
lim

## x0+ ((sin x)1 )

x0 (sin x)1
x0+ (sin x)2 cos x


sin2 x
sin x sin x
= lim+
= 1 0 = 0
= lim+

x0 x cos x
x0
x
cos x

## lim+ (sin x ln x) = lim+

x0

Solution 2: We have
lim (sin x ln x) = [0 ] =

x0+

sin x ln x
sin x ln x ln1 x
lim+
= lim+
x0
x0
1
1 ln1 x

 
sin x
0
= lim+ 1 =
x0 ln
0
x

(sin x)
cos x
cos x
ln2 x cos x
= lim+
= lim
= lim
 = lim+
2
x0
x0 ln
x (ln x) x0+ ln2 x x1 x0+ ln2 x ln2 x x1
ln1 x

hi
ln2 x
ln2 x cos x
ln2 x
ln2 x
= lim+
= lim+
= lim+
lim cos x = lim+
=

x0 (x1 )
x0
x0 x1
x0 x1 x0+
x1

= lim+
x0

2 ln x (ln x)
2 ln x x1
2 ln x x1 x
2 ln x h i
=
lim
=
lim
=
lim
=
x0+
x0+
x0+ x1
x2
x2
x2 x

2x1
20
2x1 x2
2x
(2 ln x)
=
lim
=
lim
= lim+
=
=0
= lim+

2
2
2
1
+
+
x0 x
x0 x
x0 1
x0
x
1
(x )
7

## Indeterminate Forms of Type 0, 00 and 1

13. Find lim x1/x .
x

Solution (version 1): Note that lim x1/x is 0 type of an indeterminate form. Put
x

y = x1/x
then
ln y = ln x1/x =

1
ln x
ln x =
x
x

We have
(ln x)
x1
1
ln x h i
= lim
=
=
lim
=
lim
=0
x
x 1
x x
x x

x
lim

Therefore

lim x1/x = e0 = 1

## Solution (version 2): We have

lim x1/x = lim eln x

1/x

= lim e
x

ln x
x

lim

= ex

ln x
x

x/2

lim

= ex

(ln x)
x

lim

= ex

x1
1

lim

= ex x = e0 = 1

## 14. Find lim (tan x)2x .

x/2

Solution: Note that lim (tan x)2x is 0 type of an indeterminate form. Put
x/2

y = (tan x)2x
then

ln y = ln (tan x)2x = (2x ) ln(tan x)


(2x ) ln(tan x)
ln(tan x)
(2x )1 (2x ) ln(tan x)
=
=
=
1
1
(2x ) 1
(2x )1

We have

1
hi
(tan x)
[ln(tan x)]
ln(tan x)
tan x
=
lim
=
=
lim

x/2 [(2x )1 ]
x/2 (2x )1
x/2 (1)(2x )2 (2x )

lim

1
1
1
sin x cos2 x
sin x
sec2 x
1
1
cos2 x
cos x
cos x
= lim
= lim
= lim
x/2 (1)(2x )2 2
2 x/2 (2x )2
2 x/2 (2x )2
1
tan x

1
1
sin x cos x(2x )2
(2x )2
1
1
1
sin x cos x
sin x cos x
lim
=

lim
=

lim
2 x/2 (2x )2
2 x/2 (2x )2 sin x cos x(2x )2
2 x/2 sin x cos x
 

1
1
(2x )2
(2x )2
[(2x )2 ]
1
0

= lim
=

lim
=
lim
2 x/2 sin 2 cos x
2 x/2 cos x
0
2 x/2 (cos x)



2
2

1
2(2x ) (2x )
2(2x ) 2
1
1
2
= lim
= lim
=

2 x/2
sin x
2 x/2 sin x
2
sin
2
1 202
=
=0
2
1
Therefore
lim (tan x)2x = e0 = 1

x/2

In short,
y = (tan x)2x

ln y = (2x ) ln(tan x) =

ln(tan x)
(2x )1

We have
1
sec2 x
[ln(tan x)]
(2x )2
1
ln(tan x)
tan x
=
lim
=

lim
=
lim
lim

x/2 [(2x )1 ]
x/2 (1)(2x )2 2
x/2 (2x )1
2 x/2 sin x cos x
 

1
(2x )2
[(2x )2 ]
1
0
= lim
= lim
=
2 x/2 cos x
0
2 x/2 (cos x)


2

2
2(2x ) 2
1
1
2
=0
=
= lim

2 x/2 sin x
2
sin
2
2x
0
Therefore lim (tan x)
= e = 1.
x/2

x0

## Solution: Note that lim+ xx is 00 type of an indeterminate form. Put

x0

y = xx
then
x

ln y = ln x = x ln x =
We have
lim+

x0

x ln x
x1 x ln x
=
1
x1 1

ln x
x1

(ln x)
ln x h i
x1
=
lim
=
=
lim
x0+ (x1 )
x0+ x2
x1

= lim+
x0

0
x
x1 x2
= lim+
=
=0
2
2
x0 1
x x
1

Therefore
lim+ xx = e0 = 1

x0

In short,
y = xx
We have
lim+

x0

Therefore

ln y = x ln x =

ln x
x1

(ln x)
x1
ln x
=
lim
=
lim
= lim+ x = 0
x0
x1 x0+ (x1 ) x0+ x2
lim+ xx = e0 = 1

x0

x0

10

## 16. Find lim+ (tan 5x)x .

x0

Solution: Note that lim+ (tan 5x)x is 00 type of an indeterminate form. Put
x0

y = (tan 5x)x
then
x

## ln y = ln(tan 5x) = x ln(tan 5x) =

x ln(tan 5x)
x1 x ln(tan 5x)
=
1
x1 1

ln(tan 5x)
x1

We have
(ln(tan 5x))
ln(tan 5x) h i
=
lim
lim+
=
= lim+
x0+
x0
x0
x1

(x1 )
= lim+

1
tan 5x

x0

= lim+

sin 5x
cos 5x

= lim+
x0

(tan 5x)
x2

sec2 5x (5x)
= lim+
x0
x2
sec2 5x 5
x2

x0

1
tan 5x

1
5
sin 5x
x2

= lim+

sin 5x
cos 0

x0

= lim+
x0

1
tan 5x

sec2 5x 5
x2

sec2 0 5
x2

1
5 x2 sin 5x
sin 5x
x2 x2 sin 5x

 
5x2
0
(5x2 )
= lim+
= lim+
=
x0 sin 5x
x0 ( sin 5x)
0
= lim+
x0

10x
10 0
10x
= lim+
=
=0

x0 cos 5x 5
cos 5x (5x)
cos 0 5

Therefore
lim (tan 5x)x = e0 = 1

x0+

In short,
y = (tan 5x)x

ln y = x ln(tan 5x) =

ln(tan 5x)
x1

We have
ln(tan 5x)
(ln(tan 5x))
lim+
=
lim
= lim+
x0
x0+
x0
x1
(x1 )
= lim+
x0

1
5
sin 5x
2
x

= lim+
x0

1
tan 5x

sec2 5x 5
= lim+
x0
x2

1
sin 5x
cos 5x

sec2 5x 5
x2

5x2
(5x2 )
10x
= lim+
= lim+
=0

x0 cos 5x 5
sin 5x x0 ( sin 5x)

Therefore
lim+ (tan 5x)x = e0 = 1

x0

11

## 17. Find lim+ (sin 2x)tan 3x .

x0

Solution: Note that lim+ (sin 2x)tan 3x is 00 type of an indeterminate form. Put
x0

y = (sin 2x)tan 3x
then


sin 3x ln(sin 2x)
ln y = ln (sin 2x)tan 3x = tan 3x ln(sin 2x) =
cos 3x

We have

## lim (sin 3x ln(sin 2x))

sin 3x ln(sin 2x)
x0+
lim
= lim+ (sin 3x ln(sin 2x)) = [0 ]
=
x0+
x0
cos 3x
lim+ cos 3x
x0

## sin 3x ln(sin 2x)

(sin 3x)1 sin 3x ln(sin 2x)
lim
= lim+
x0+
x0
1
(sin 3x)1 1

= lim+
x0

ln(sin 2x) h i
= lim+
=
x0 (sin 3x)1

## sin1 2x cos 2x (2x)

sin1 2x (sin 2x)
[ln(sin 2x)]
=
lim
=
lim
((sin 3x)1 ) x0+ (sin 3x)2 (sin 3x) x0+ (sin 3x)2 cos 3x (3x)

2
2
sin1 2x
cos 2x
sin1 2x
sin1 2x cos 2x 2
= lim+
lim
= lim+
= lim+
x0 (sin 3x)2 cos 3x 3
3 x0 (sin 3x)2 x0+ cos 3x
3 x0 (sin 3x)2
 
2
2
0
2
sin1 2x sin 2x sin2 3x
sin2 3x
(sin2 3x)
= lim+
=

lim
=
lim
3 x0 (sin 3x)2 sin 2x sin2 3x
3 x0+ sin 2x
0
3 x0+ (sin 2x)
=

## 2 sin 3x (sin 3x)

2 sin 3x cos 3x (3x)
2
2
lim+
=

lim
3 x0
cos 2x (2x)
3 x0+
cos 2x 2

2
2 2 sin 0 cos 0 3
2 2013
2 sin 3x cos 3x 3
lim+
=
=
=0
3 x0
cos 2x 2
3
cos 0 2
3
12

Therefore

## lim (sin 2x)tan 3x = e0 = 1

x0+

In short,
y = (sin 2x)tan 3x

## sin 3x ln(sin 2x)

cos 3x

We have
lim+

x0

ln(sin 2x)
[ln(sin 2x)]
sin 3x ln(sin 2x)
= lim+ (sin 3x ln(sin 2x)) = lim+
=
lim

x0
x0 (sin 3x)1
x0+ ((sin 3x)1 )
cos 3x

= lim+
x0

sin1 2x cos 2x 2
2
2
2
sin1 2x
sin2 3x
(sin2 3x)
=

lim
=

lim
=

lim
(sin 3x)2 cos 3x 3
3 x0+ (sin 3x)2
3 x0+ sin 2x
3 x0+ (sin 2x)

2 2 sin 0 cos 0 3
2 sin 3x cos 3x 3
2
lim+
=
=0
3 x0
cos 2x 2
3
cos 0 2

x0

12

x+1
x+2

x

then

x+1
x+2

x

## is 1 type of an indeterminate form. Put y =

x+1
x+2

x








x+1
x+1
x+1

1
ln

x 


x x ln
x ln x + 2
x+1
x+1
x+2
x+2
ln y = ln
= x ln
=
=
=
1

x+2
x+2
1
x 1
x1

We have





 
x+1
1
x+1
x+1
 
ln
ln
x+1
x+2
0
x+2
x+2
lim
= lim
=
= lim x+2
1
1

x
x
x
x
0
(x )
x2

x + 2 1 (x + 2) 1 (x + 1)
x + 2 (x + 1) (x + 2) (x + 1)(x + 2)

2
x+1
(x + 2)
x+1
(x + 2)2
=
lim
= lim
x
x
x2
x2

x+2 x+2x1
1
x+2
1

2
2
x+1
(x + 2)
x + 1 (x + 2)
(x + 1)(x + 2)
= lim
= lim
= lim
2
2
x
x
x
x
x
x2
1
x2 (x + 1)(x + 2)
hi
x2
x2
(x + 1)(x + 2)
=

lim
=
lim
=
= lim
x x2 + 3x + 1
x (x + 1)(x + 2)
x
x2 x2 (x + 1)(x + 2)

x2
x2
2
1
1
x2
= 1
= lim 2 x
= lim 2
= lim
=
3
1
x x + 3x + 1
x x
x
1+0+0
3x
1
1+ + 2
+ 2 + 2
x x
x2
x2
x
x
Therefore

x
x+1
lim
= e1
x x + 2
In short,


x+1
x
 ln


x+1
x+1
x+2
=
y=
= ln y = x ln
x+2
x+2
x1
We have



 
x+1
x+1
1
x+2
ln
ln

x2
x+2
x+2
x + 1 (x + 2)2
lim
=
lim
=
lim
=

lim
x
x
x
x (x + 1)(x + 2)
x1
(x1 )
x2
x2
= 1
x x2 + 3x + 1

= lim
Therefore lim

x+1
x+2

x

= e1 .
13

## 2010 Kiryl Tsishchanka

Solution 2: We have
lim

x+1
x+2

x

= lim

x+21
x+2

x

1
x+2

= lim
x x + 2
x+2
x

1
= lim 1
x
x+2

= lim 1 +
x

1
x 2

"
= lim
1+
x

x

x
(x2) x2

1
x 2

x
x2 # x2


u
x2

1
1
Since lim 1 +
= e, it follows that lim 1 +
= e. Therefore
u
x
u
x 2
x
"

x
x2 # x2
x+1
1
lim
1+
= lim
x x + 2
x
x 2
x

= lim e x2
x

lim

= ex x2
x

lim

= ex (x2)
= e1
COMPARE: We have
lim

since

x+1
3x + 2

1
x+1
=
lim
x 3x + 2
3

Similarly,
lim

since

3x + 1
x+2

and
x

3x + 1
= 3 and
x x + 2

x

=0

 x
1
=0
lim
x 3

= (D.N.E.)
lim 3x = (D.N.E.)

lim

x

1
19. Find lim 1 +
.
x
x
14

## 2010 Kiryl Tsishchanka


x
1
19. Find lim 1 +
.
x
x
Solution: We have


x
1
lim 1 +
=e
x
x

by definition of e. Note, that we cant use the approach described in Example 13, since
 it isbased
x
1
1

of the formula (ln x) = . But this result was deduced from the fact that lim 1 +
=e
x
x
x
(see Appendix A). This is Circular Reasoning which is a logical fallacy. However, one can apply
LHospitals Rule to modifications of this limit.
20. Find lim+ (1 + sin 7x)cot 5x .
x0

Solution: Note that lim+ (1 + sin 7x)cot 5x is 1 type of an indeterminate form. Put
x0

y = (1 + sin 7x)cot 5x
then


cos 5x ln(1 + sin 7x)
ln y = ln (1 + sin 7x)cot 5x = cot 5x ln(1 + sin 7x) =
sin 5x

We have

lim+

x0

## ln(1 + sin 7x)

cos 5x ln(1 + sin 7x)
= lim+ cos 5x lim+
x0
x0
sin 5x
sin 5x

 
ln(1 + sin 7x)
[ln(1 + sin 7x)]
0
= lim+
= lim+
=
= lim+
x0
x0
x0
sin 5x
0
(sin 5x)
= lim+

1
1+sin 7x

x0

cos 7x (7x)
= lim+
x0
cos 5x 5

1
1+sin 7x

cos 7x 7
=
cos 5x 5

1
1+sin 7x

(1 + sin 7x)
cos 5x (5x)

1
1+0

17
7
=
15
5

Therefore
lim (1 + sin 7x)cot 5x = e7/5

x0+

In short,
y = (1 + sin 7x)cot 5x

sin 5x

We have
lim+

x0

ln(1 + sin 7x)
[ln(1 + sin 7x)]
= lim+
= lim+
x0
x0
sin 5x
sin 5x
(sin 5x)
= lim+

1
1+sin 7x

cos 7x 7
=
cos 5x 5

x0

x0

15

1
1+0

17
7
=
15
5

## 2010 Kiryl Tsishchanka

Appendix A
THEOREM: The function f (x) = sin x is differentiable and
f (x) = cos x
Proof: We have
sin(x + h) sin x
h0
h

(sin x) = lim

## [We use sin( + ) = sin cos + cos sin ]



sin x cos h sin x cos x sin h
sin x cos h + cos x sin h sin x
= lim
= lim
+
h0
h0
h
h
h


cos h 1
sin h
sin h
sin x(cos h 1)
= sin x lim
+ cos x
+ cos x lim
= lim
h0
h0 h
h0
h
h
h
= sin x 0 + cos x 1 = cos x
THEOREM: The function f (x) = loga x is differentiable and
f (x) =

1
x ln a

Proof: We have



1
x+h
loga (x + h) loga x
d
(loga x) = lim
= lim
loga
h0
h0 h
dx
h
x







1
1 x
h
h
= lim
= lim
loga 1 +
loga 1 +
h0 h
h0 x h
x
x
"
"


x/h #
1/(h/x) #
h
h
1
1
= lim loga 1 +
= lim loga 1 +
x h0
x
x h0
x
"

1/(h/x) # h
i 1
h
1
1 ln e
1
= lim (1 + u)1/u = e = loga e =
= loga lim 1 +
=
u0
h0
x
x
x
x ln a
x ln a

16

## 2010 Kiryl Tsishchanka

Appendix B
1. Find lim

x0

sin x
.
2x

Solution 1: We have
 
cos 0
1
(sin x)
0
sin x
cos x
= lim
lim
=
= lim
=
=

x0
x0
x0 2x
0
(2x)
2
2
2
Solution 2: We have

 
1
1
1
0
sin x
sin x
= lim
=
= 1=
lim
x0 2x
0
2 x0 x
2
2

sin 2x
.
x0
x

2. Find lim

Solution 1: We have
 
2 cos 0
(sin 2x)
0
2 cos 2x
sin 2x
= lim
=
= lim
=
=2
lim

x0
x0
x0
x
0
x
1
1
Solution 2: We have

 
0
sin 2x
sin 2x
= 2 lim
=
=21=2
lim
x0
x0
x
0
2x

sin 2x
.
x0 5x

3. Find lim

Solution 1: We have
 
sin 2x
0
2 cos 0
2
(sin 2x)
2 cos 2x
lim
= lim
=
=
lim
=
=
x0 5x
x0 (5x)
x0
0
5
5
5
Solution 2: We have

 
2
0
2
2
sin 2x
sin 2x
= lim
=
= 1=
lim
x0 5x
0
5 x0 2x
5
5

sin 2x
.
x0 sin 5x

4. Find lim

Solution 1: We have
 
0
2 cos 0
2
(sin 2x)
2 cos 2x
sin 2x
= lim
=
= lim
=
=
lim

x0 (sin 5x)
x0 5 cos 5x
x0 sin 5x
0
5 cos 0
5
Solution 2: We have
 
0
sin 2x
= lim
=
lim
x0
x0 sin 5x
0

sin 2x
2x
sin 5x
5x

2x
2
2
1 2x
= lim =
= lim
x0
x0
1 5x
5
5
5x

17